Building Research Tools with Google for Dummies - Davis, Harold (Wiley Publishing, 2011)
Google—a funny name for a fabulous tool. You’ve already used it to look up all sorts of information on the Web almost instantly. Now what if you could use its amazing abilities to turbo-charge your research on a grand scale?